Volcán Taburiente Digital Outcrop Models - Thiele, Samuel; Cruden, Alexander; Micklethwaite, Steven (Monash University, 2019)
A collection of digital outcrop models constructed using unmanned aerial vehicle (UAV) photogrammetry and used to quantify the geometry and distribution of intrusions within the shallow plumbing system of Volcán Taburiente, La Palma (Canary Islands, Spain). A detailed description and analysis is included in my PhD thesis at: https://doi.org/10.26180/5dd7263c09ac1 Overview: Please refer to Dataset_Overview.pdf/pptx for an overview of each of the surveys including descriptions of:1. their extent and location2. ground sampling distance3. features of interest Point clouds: The aligned and interpreted point clouds from each survey area have been included as CloudCompare .bin files in _point_clouds_only.zip . CloudCompare can be freely downloaded here: http://www.cloudcompare.org/ and used to (1) view the data and interpretation and (2) export it to other point cloud or raster formats. Structural measurements: Measurements of dyke orientation and thickness have been exported from CloudCompare to an easily readable .xml format and stored in _structural_measurements_only.zip . Example code for loading, plotting and analysing these data can be found here: https://github.com/samthiele/pycompass Complete surveys: Complete datasets are included in the other .zip files, named according to the area they cover. Each of these includes:1. UAV images (.jpg)2. Agisoft Photoscan files3. LAZ point clouds4. Orthophoto rasters5. Digital elevation models6. aligned and interpreted point clouds (.bin) Unprocessed Surveys: UAV images from surveys that were acquired but have not been processed are included in 12_Unprocessed Images.zip . 3D Point Cloud Previews Point clouds from each survey can be previewed in a web browser via the following links: Las Pareditas 1: https://mivp-dws1.erc.monash.edu:3000/pointviewer/?tag=92f3bbLas Pareditas 2: https://mivp-dws1.erc.monash.edu:3000/pointviewer/?tag=456518Las Pareditas 3: https://mivp-dws1.erc.monash.edu:3000/pointviewer/?tag=866a5b Risco Liso Summit: https://mivp-dws1.erc.monash.edu:3000/pointviewer/?tag=b27b39Risco Liso Cliff: https://mivp-dws1.erc.monash.edu:3000/pointviewer/?tag=d2fde7 Hoyo Verde Alto: https://mivp-dws1.erc.monash.edu:3000/pointviewer/?tag=c12b12Hoyo Verde Cliff: https://mivp-dws1.erc.monash.edu:3000/pointviewer/?tag=680e05Hoyo Verde Rio: https://mivp-dws1.erc.monash.edu:3000/pointviewer/?tag=35bbb4 Los Cantos 1: https://mivp-dws1.erc.monash.edu:3000/pointviewer/?tag=a116e8Los Cantos 2: https://mivp-dws1.erc.monash.edu:3000/pointviewer/?tag=f9af0d Los Andenes Norte: https://mivp-dws1.erc.monash.edu:3000/pointviewer/?tag=bdc8beLos Andenes Sur: https://mivp-dws1.erc.monash.edu:3000/pointviewer/?tag=9a2d3d Stegosaurus Ridge: https://mivp-dws1.erc.monash.edu:3000/pointviewer/?tag=323577Dishwasher Ridge: https://mivp-dws1.erc.monash.edu:3000/pointviewer/?tag=26197eLa Cumbrecita: https://mivp-dws1.erc.monash.edu:3000/pointviewer/?tag=6cd33fBejenado Lava Worm: https://mivp-dws1.erc.monash.edu:3000/pointviewer/?tag=4f5c0aSocomo: https://mivp-dws1.erc.monash.edu:3000/pointviewer/?tag=6b9d5a